The rare travellers - Mittal, Vinamra; Ghildiyal, Divyanshu; Sachan, P. K. (International Surgery Journal, 2021)
Hernia surgery constitutes one of the major daily operative procedures in the general surgery department. Using of mesh with tension free repair is the most widely used technique. Mesh migration and subsequent perforation account as one of the very rare complications following laparoscopic or open hernia repair. The complications following surgery present with symptoms at different time intervals and are sometimes very difficult to diagnose. We present here a couple of cases of mesh migration resulting in varied clinical symptoms and a diagnostic dilemma. With more emphasis being on non-fixation of meshes in the recent literatures, a lower clinical and diagnostic threshold should be incorporated in diagnosing such complications.